2012
DOI: 10.1016/j.jinf.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Is the discovery of the novel human betacoronavirus 2c EMC/2012 (HCoV-EMC) the beginning of another SARS-like pandemic?

Abstract: Fouchier et al. reported the isolation and genome sequencing of a novel coronavirus tentatively named "human betacoronavirus 2c EMC/2012 (HCoV-EMC)" from a Saudi patient presenting with pneumonia and renal failure in June 2012. Genome sequencing showed that this virus belongs to the group C species of the genus betacoronavirus and phylogenetically related to the bat coronaviruses HKU4 and HKU5 previously found in lesser bamboo bat and Japanese Pipistrelle bat of Hong Kong respectively. Another patient from Qat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
141
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 99 publications
1
141
0
5
Order By: Relevance
“…Two bat CoVs from lineage group C, BtCoV-HKU4 and BtCoV-HKU5, are the most closely related to the MERS-CoV. 2, 79 MERS-CoV and SARS-CoV are highly pathogenic, with evidence of person-to-person transmission via either household or hospital contacts. 10, 11 MERS-CoV and SARS-CoV use different receptors, dipeptidyl peptidase 4 (DPP4 or CD26) and angiotensin-converting enzyme 2 (ACE2), respectively, 12, 13 and the epidemiology of MERS-CoV is still being investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two bat CoVs from lineage group C, BtCoV-HKU4 and BtCoV-HKU5, are the most closely related to the MERS-CoV. 2, 79 MERS-CoV and SARS-CoV are highly pathogenic, with evidence of person-to-person transmission via either household or hospital contacts. 10, 11 MERS-CoV and SARS-CoV use different receptors, dipeptidyl peptidase 4 (DPP4 or CD26) and angiotensin-converting enzyme 2 (ACE2), respectively, 12, 13 and the epidemiology of MERS-CoV is still being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Both MERS-CoV and SARS-CoV exhibit as a severe respiratory infection, while MERS-CoV exhibits an additional unique symptom of renal failure. 2 Even though the MERS-CoV transmission rate is slower than that of SARS-CoV, the number of MERS-CoV infections continues to grow. 11, 14, 15 Due to the recent emergence of this new coronavirus and the potential of SARS-CoV retransmission from zoonotic reservoirs to humans, 1618 the possibility of another deadly pandemic has been seriously raised.…”
Section: Introductionmentioning
confidence: 99%
“…they consist of single-stranded positive-sense, nonsegmented genomes (ChaN et al, 2012). Middle east respiratory syndrome coronavirus (MerS-CoV) is a novel coronavirus which emerged (ZakI et al, 2012) link to the Middle East, with confirmed cases in Iran, Jordan, Kuwait, Lebanon, Oman, Saudi arabia, Qatar, United arab emirates and Yemen.…”
Section: Introductionmentioning
confidence: 99%
“…1 Focusing on atypical clinical presentations of novel Middle East respiratory syndrome, the renal failure is an important presentation. 1,3 In almost all death cases, acute renal failure can be identified. 1,3,4 Focusing on the course, the patients usually starts with acute febrile illness with rapid progression to severe respiratory distress syndrome then acute renal failure occurs on top.…”
mentioning
confidence: 99%
“…1,3,4 Focusing on the course, the patients usually starts with acute febrile illness with rapid progression to severe respiratory distress syndrome then acute renal failure occurs on top. 1,3,4 This nature is a significant difference from the already known SARS, of which, no predominant renal failure can be observed. The underlying cause of acute renal failure in novel Middle East respiratory syndrome is still the myth.…”
mentioning
confidence: 99%